Streptomycetes: Attractive Hosts for Recombinant Protein Production - Berini, Francesca; Marinelli, Flavia; Binda, Elisa (Frontiers in Microbiology, 2020)
Enzymes are increasingly applied as biocatalysts for fulfilling industrial needs in a variety of applications and there is a bursting of interest for novel therapeutic proteins. Consequently, developing appropriate expression platforms for efficiently producing such recombinant proteins represents a crucial challenge. It is nowadays widely accepted that an ideal ‘universal microbial host’ for heterologous protein expression does not exist. Indeed, the first-choice microbes, as Escherichia coli or yeasts, possess known intrinsic limitations that inevitably restrict their applications. In this scenario, bacteria belonging to the Streptomyces genus need to be considered with more attention as promising, alternative, and versatile platforms for recombinant protein production. This is due to their peculiar features, first-of-all their natural attitude to secrete proteins in the extracellular milieu. Additionally, streptomycetes are considered robust and scalable industrial strains and a wide range of tools for their genetic manipulation is nowadays available. This mini-review includes an overview of recombinant protein production in streptomycetes, covering nearly a hundred cases of heterologous proteins expressed in these Gram-positives from the 1980s to December 2019. We investigated homologous sources, heterologous hosts, and molecular tools (promoters/vectors/signal peptides) used for the expression of these recombinant proteins. We reported on their final cellular localization and yield. Thus, this analysis might represent a useful source of information, showing pros and cons of using streptomycetes as platform for recombinant protein production and paving the way for their more extensive use in future as alternative heterologous hosts.